2020
DOI: 10.1093/ofid/ofaa268
|View full text |Cite
|
Sign up to set email alerts
|

Influenza With and Without Fever: Clinical Predictors and Impact on Outcomes in Patients Requiring Hospitalization

Abstract: Abstract Background The Infectious Diseases Society of America influenza guidelines no longer require fever as part of their influenza case definition in patients requiring hospitalisation. However, the impact of fever or lack of fever on clinical decision-making and patient outcomes has not been studied. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…To our knowledge, there is only very limited data exploring this comparison, 9 and our paper is one of the first to link key presenting phenotypes with diagnostic patterns and timing of PCR testing. 10 We found that those presenting with influenza were far more likely to be febrile, whereas only a minority of RSV patients were febrile. The RSV group was significantly more likely to be tachypnoeic and less likely to be shocked as indicated by systolic hypotension.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To our knowledge, there is only very limited data exploring this comparison, 9 and our paper is one of the first to link key presenting phenotypes with diagnostic patterns and timing of PCR testing. 10 We found that those presenting with influenza were far more likely to be febrile, whereas only a minority of RSV patients were febrile. The RSV group was significantly more likely to be tachypnoeic and less likely to be shocked as indicated by systolic hypotension.…”
Section: Discussionmentioning
confidence: 64%
“…An important pattern demonstrated in this paper was the key comparative differences in clinical phenotype between influenza and RSV. To our knowledge, there is only very limited data exploring this comparison, 9 and our paper is one of the first to link key presenting phenotypes with diagnostic patterns and timing of PCR testing 10 . We found that those presenting with influenza were far more likely to be febrile, whereas only a minority of RSV patients were febrile.…”
Section: Discussionmentioning
confidence: 65%
“…One study found older adults (N = 1,318), presented to the emergency department with influenza 2-5 days after symptom onset (14). In other studies, seeking treatment occurred up to 1 week after symptom onset (15,16). This delay in seeking health care increases their mortality risk (14).…”
Section: Temperature and Older Adultsmentioning
confidence: 99%
“…This delay in seeking health care increases their mortality risk (14). Therefore, the objective measure of a temperature and the threshold of 100.4 F as a fever indicator does not provide a sufficient indicator of infection in older adults and may delay the diagnosis and treatment for COVID-19 (15,16).…”
Section: Temperature and Older Adultsmentioning
confidence: 99%
“…The largest number of studies has evaluated isolated risk factors leading to lethal outcome and only a few of them have been focused on the complete palette of predictors for development of a severe form of the disease and lethal outcome [9][10][11][12][13][14][15][16]. From the clinical practice point of view, the awareness/recognition of the risk factors and predictors for lethal outcome of influenza is of particular importance in bringing timely and exact decision for hospitalization, treatment or undertaking special measures for intensive monitoring of these patients.…”
Section: Introductionmentioning
confidence: 99%